Mentoring EFL Learners Beyond the Formal Classroom Context - Giri, Prakash Chandra (Journal of Interdisciplinary Studies, 2025)
Mentoring beyond the formal classroom context has been a good practice for relational experience for both EFL teachers and learners around the world. As it is an emerging practice here in Nepal, this has brought an enlightenment on the relationship between teachers and students. This study displays an emerging practice of mentoring in EFL within the Nepali context. Carrying out semi-structured interviews with five English educators and three students from national and international institutions, the research reveals that mentoring beyond the formal classroom context offers a significant benefit such as teacher-student rapport, enhanced motivation, improvement on the language confidence. The research also demonstrates some challenges such as limited exposure and practice, time management and lack of institutional initiatives. The B.Ed English syllabus does not include the mentoring as a professional development for teacher trainers too which trains a lot of teacher trainees all over Nepal. The research recommends for a planned relationship- based mentoring practice focusing on the enhancement for both teachers and students. This research suggests educators, stakeholders, policymakers to intergrade intentional mentoring practice within the formal and beyond the formal EFL classroom context in Nepal.